Pengembangan Aplikasi Media Pembelajaran Berbasis Game Edukasi Tanaman Obat dan Herbal Madura - Juwita Nurqomariah; Muhlis Tahir (Jurnal Masyarakat Informatika, 2024)
This study aims to develop an educational game-based learning media application that introduces medicinal plants and Madurese herbs to class X students majoring in Pharmacy at SMKS Yannas Husada Bangkalan. This application is expected to improve students' understanding of simplisia, herbs, and rhizomes in Pharmacognosy subjects, as well as foster higher interest in learning through an interactive and technology-based approach. Application development uses the Multimedia Development Life Cycle (MDLC) model which consists of six stages, namely concept, design, material collecting, assembly, testing, and distribution. The test results from media experts showed that this application reached an achievement level of 88% and was very feasible to use. Assessment from material experts also showed an achievement of 88.89%, indicating that this application is valid and suitable for use. In addition, testing conducted by class X students majoring in Pharmacy at SMKS Yannas Husada Bangkalan showed an achievement level of 93%, which also indicates that this application is very feasible to use. Based on these results, it can be concluded that this application is effective and valid to be used as a learning media.